Gender Differences in Millennial Consumers of Latin America Associated with Conspicuous Consumption of New Luxury Goods - Ponce-Arias, H (Sage Publications India Pvt. Ltd, 2023)
Conspicuous consumption has been studied in the millennial generation in the United States and Asia; in Latin America, however, it has scarcely been analysed. The purpose of this study is to examine whether conspicuous motivations in millennial consumers are more prominent in men than in women associated with the consumption of new luxury goods in Latin America. A survey was developed to measure conspicuous motivation, more specifically, bandwagon and snob effects. It was responded by 712 university students located in five different cities in Chile. The findings of the study showed that the bandwagon and snob motivations were higher in men than in women. Men also showed a greater tendency than women to purchase and use new luxury products in social contexts. These results suggest that managers could adjust their marketing strategies to better target millennial consumers of new luxury products. © 2022 IMI.